2001
DOI: 10.1159/000054910
|View full text |Cite
|
Sign up to set email alerts
|

Association Study for a Functional Serotonin Transporter Gene Polymorphism and Late-Onset Alzheimer’s Disease for Chinese Patients

Abstract: Two recent studies have demonstrated an association for a deletion/insertion polymorphism within the promoter region of the serotonin transporter gene (5-HTTLPR), and Alzheimer’s disease (AD). According to these studies, subjects with the short variant of the 5-HTTLPR gene are at increased risk for AD; however, this finding has not been confirmed by other workers. To evaluate the role of the 5-HTTLPR gene in susceptibility for AD, we conducted an association study for this polymorphism in a Chinese population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…These results suggested that the association between 5-HTTL-PR polymorphism and AD might vary according to the different ethnicities. The s allelic frequency in this study sample (73-75%) was similar to the results of other studies with Asian populations (72-80%) [8,10] , but it was much higher than those from the studies with Caucasian populations (40-50%) [5][6][7] . If the s allele is a risk factor for AD, the prevalence of AD should be higher in Asian populations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results suggested that the association between 5-HTTL-PR polymorphism and AD might vary according to the different ethnicities. The s allelic frequency in this study sample (73-75%) was similar to the results of other studies with Asian populations (72-80%) [8,10] , but it was much higher than those from the studies with Caucasian populations (40-50%) [5][6][7] . If the s allele is a risk factor for AD, the prevalence of AD should be higher in Asian populations.…”
Section: Discussionsupporting
confidence: 87%
“…A striking feature of research on the association between 5-HTTLPR polymorphism and AD was the confl icting fi ndings according to the sampled populations. Studies conducted in England [5] , Brazil [6] and Germany [7] reported signifi cant associations, while others from Japan [8] , Germany [9] and China [10] found no associations. Two of the 3 studies reporting the negative fi ndings were based on oriental populations, which was in keeping with the result of the present study with Koreans.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Genotype frequencies in both groups were in Hardy-Weinberg equilibrium. The frequency of short allele in healthy subjects (71%) was similar to that reported in other Chinese population (Tsai et al, 2001). However, the frequency of short/short genotype observed in the GAD patients was higher than that in healthy subjects (68% versus 49%, w 2 = 12.274, df = 2, P = 0.002), and the frequency of short allele in GAD patients was higher than that in controls (79 versus 71%, w 2 = 4.063, df = 1, P = 0.044).…”
Section: -Httlpr Polymorphismsupporting
confidence: 88%
“…The 12 excluded papers included 6 studies that did not examine healthy controls, and 6 reviews and brief reports. Five case-control datasets were included in the meta-analysis of the Asian population, which included 524 cases and 699 controls [24,26,52,53]. Ten case-control datasets were included in the meta-analysis of the Caucasian population, which included 1,436 cases and 1,342 controls.…”
Section: Resultsmentioning
confidence: 99%